Test Type's Knife In Tools Fruit Pickers - Sari Azhira Siregar; Saipul Bahri Daulay; Sulastri Panggabean; Riswanti Sigalingging (Universitas Sumatera Utara, 2013)
This study is on a test of the type of blade ofl fruit picker tool. This study was conducted to test the type ofblade of fruit picker tool using tamarind , melinjo, and rambutan trees to determine the effective capacity,field capacity, percentage of defects of the tool and the level of operator fatigue. The research was conductedin Tridharma, A. H. Nasution and Bunga Mawar Roads from February to August 2012 with tworeamentsnamely blade and fruit. Blade disc, blade star, blade rotary and rambutan, melinjo and tamarind.The results showed that various type of blade had highly significant effect the field capacity and thepercentage of damaged fruit but had no significant effects on the the effective capacity of the tool. Fruit typehad significant effect on the field capacity. The best type of blade of was disc blade with 16.91 kg h and percentage of 4.90% the smallest percentage of fruit damage found in melinjo with disc blade that is equa1,5%.-1